Qur'ans of the Umayyads A First Overview - Déroche, François (Leiden Studies in Islam and Society, 2013)
For the first time, the dramatic changes the Qur'anic code underwent during the Umayyad period (660-750 C.E.) are analysed and presented on the basis of a selection of material in good part unpublished. Winner of 23rd I.R. Iran World Award for the Book of the Year 2016!